Alcohol Use Disorders Are Associated With a Unique Impact on Airway Epithelial Cell Gene Expression. (1st July 2020) - Bailey, Kristina L.; Smith, Harry; Mathai, Susan K.; Huber, Jonathan; Yacoub, Mark; Yang, Ivana V.; Wyatt, Todd A.; Kechris, Katerina; Burnham, Ellen L.
Abstract : Background: Alcohol use disorders (AUDs) and cigarette smoking both increase risk for the development of community‐acquired pneumonia (CAP), likely through adverse effects on proximal airway mucociliary clearance and pathogen recognition. Smoking‐related alterations on airway gene expression are well described, but little is known about the impact of AUDs. We measured gene expression in human airway epithelial cells (AECs), hypothesizing that AUDs would be associated with novel differences in gene expression that could alter risk for CAP. Methods: Bronchoscopy with airway brushings was performed in participants with AUDs and controls to obtain AECs. An AUD Identification Test was used to define AUD. RNA was extracted from AECs, and mRNA expression data were collected on an Agilent micro‐array. Differential expression analyses were performed on the filtered and normalized data with correction for multiple testing. Enrichment analyses were performed using clusterProfiler. Results: Expression data from 19 control and 18 AUD participants were evaluated. After adjustment for smoking, AUDs were associated with significant differential expression of 520 AEC genes, including genes for ribosomal proteins and genes involved in protein folding. Enrichment analyses indicated significant differential expression of 24 pathways in AUDs, including those implicated in protein targeting to membrane and viral gene expression. Smoking‐associated AEC gene expression differences mirrored previous reports, but differed from those associated with AUDs. Conclusions: AUDs have a distinct impact on AEC gene expression that may influence proximal airway function independent of smoking. Alcohol‐associated alterations may influence risk for CAP through modifying key mechanisms important in protecting proximal airway integrity. Abstract : Harmful alcohol use has been linked to development of pneumonia, a major cause for hospitalization and the most common cause for sepsis and septic shock. Alcohol use has been linked to abnormalities in upper airway mucociliary clearance that may be partly to blame. In human airways epithelial cells from participants with harmful alcohol use, we observed novel gene expression differences independent of cigarette smoking that may alter risk for pneumonia through compromising mechanisms important in maintaining airways integrity.